REPENSER QUELQUES RATÉS COMMUNICATIONNELS EN POLITIQUE POUR LA PAIX EN ITURI - Batsu, Henri-Paul IYELE (IJRDO - Journal of Social Science and Humanities Research, 2022)
Lake of peace question at Ituri and North Kivu annoyed inhabitant of that region, Democratic Republic of Congo and African great lakes region. Reason why, it is important that Democratic Republic of Congo’s central government, besides political and military mechanism established security in Ituri province, agonized by recrudescence of strange armies’ nature conflicts, rethinks on his politics of negotiation with all actors who directly or indirectly involved in war.It can be local population, ethnics with conflicts, great lake states, responsibles of armies groups, civil society and international communities including multinationals for a large frame of dialogue. So, without peace in that region with enormous economic, security and environmental issues, Congolese government with unique military option could not establish peace, guarantee of society development.This large frame of dialogue could recall to all social intelligences, political, diplomatic, military and economic for a positive peace orientated at the well-being and full development of Democratic Republic of Congo, in general and in Ituri Province, in particular.